Influenza, but not SARS‐CoV‐2, infection induces a rapid interferon response that wanes with age and diminished tissue‐resident memory CD8+ T cells. Issue 1 (26th January 2021) - Nguyen, Thi HO; McAuley, Julie L; Kim, Youry; Zheng, Ming ZM; Gherardin, Nicholas A; Godfrey, Dale I; Purcell, Damian FJ; Sullivan, Lucy C; Westall, Glen P; Reading, Patrick C; Kedzierska, Katherine; Wakim, Linda M
Abstract: Older individuals exhibit a diminished ability to respond to and clear respiratory pathogens and, as such, experience a higher rate of lung infections with a higher mortality rate. It is unclear why respiratory pathogens impact older people disproportionately. Using human lung tissue from donors aged 22–68 years, we assessed how the immune cell landscape in lungs changes throughout life and investigated how these immune cells respond following in vitro exposure to influenza virus and SARS‐CoV‐2, two clinically relevant respiratory viruses. While the frequency of most immune cell subsets profiled in the human lung remained stable with age, memory CD8 + T cells declined, with the tissue‐resident memory (Trm) CD8 + T‐cell subset being most susceptible to age‐associated attrition. Infection of lung tissue with influenza virus resulted in an age‐associated attenuation in the antiviral immune response, with aged donors producing less type I interferon (IFN), GM‐CSF and IFNγ, the latter correlated with a reduction of IFNγ‐producing memory CD8 + T cells. In contrast, irrespective of donor age, exposure of human lung cells to SARS‐CoV‐2, a pathogen for which all donors were immunologically naïve, did not trigger activation of local immune cells and did not result in the induction of an early IFN response. Our findings show that the attrition of tissue‐bound pathogen‐specific Trm in the lung that occurs with advanced age, or their absence in immunologically naïve individuals, results in a diminished early antiviral immune response which creates a window of opportunity for respiratory pathogens to gain a greater foothold. Abstract : We observed an age‐associated decline of lung‐resident memory CD8 + T cells in the elderly. The loss of the resident memory T‐cell pool that occurs with advanced age coincided with an impairment in the early antiviral immune response following exposure to influenza virus and SARS‐CoV‐2, a phenomenon that may, in part, explain the increased vulnerability of the elderly to respiratory infections.